I would certainly never call it a plague." Linguistic reflections of contagion (Altre Modernità, 2023)
This contribution reflects on the way epidemic contagion was described in the Renaissance, using as sources the vernacular plague treatises published in Italy between the 15th and 16th centuries; in the last part, some considerations are made regarding the linguistic repercussions of the 2020 Covid epidemic.
Keywords: History of Italian language; specialist languages; Renaissance; Medicine; Plague